Evaluation of certain food additives and contaminants : sixty-eighth report of the Joint FAO/WHO Expert Committee on Food Additives (World Health Organization, 2007)
This report represents the conclusions of a Joint FAO/WHO Expert Committee convened to evaluate the safety of various food additives, including flavoring agents with a view to recommending acceptable daily intakes (ADIs) and to preparing specifications for identity and purity. The Committee also evaluated the risk posed by two food contaminants with the aim of advising on risk management options for the purpose of public health protection. The first part of the report contains a general discussion of the principles governing the toxicological evaluation and assessment of intake of food additives (in particular flavoring agents) and contaminants. A summary follows of the Committee s evaluations of technical, toxicological, and intake data for certain food additives (acidified sodium chlorite asparaginase from Aspergillus oryzae expressed in Aspergillus oryzae, carrageenan and processed Eucheuma seaweed, cyclotetraglucose and cyclotetraglucose syrup, isoamylase from Pseudomonas amyloderamosa, magnesium sulfate, phospholipase A1 from Fusarium venenatum expressed in Aspergillus oryzae, sodium iron(III), ethylenediaminetetraacetic acid (EDTA), and steviol glycosides); eight groups of related flavoring agents (linear and branched-chain aliphatic unsaturated, unconjugated alcohols, aldehydes, acids and related esters; aliphatic acyclic and alicyclic terpenoid, tertiary alcohols and structurally related substances; simple aliphatic and aromatic sulfides and thiols; aliphatic acyclic diols, triols and related substances; aliphatic acetals; sulfur-containing heterocyclic compounds; aliphatic and aromatic amines and amides; and aliphatic alicyclic linear a b-unsaturated di- and trienals and related alcohols acids and esters); and two food contaminants (aflatoxin and ochratoxin A). Specifications for the following food additives were revised: maltol and ethyl maltol nisin preparation pectins polyvinyl alcohol and sucrose esters of fatty acids. Specifications for the following flavouring agents were revised: maltol and ethyl maltol maltyl isobutyrate 3-acetyl-2 5-dimethylfuran and 2 4 5-trimethyl-delta-oxazoline (No. 1482, 1506, and 1559) and monomenthyl glutarate (No. 1414), as well as the method of assay for the sodium salts of certain flavoring agents. Annexed to the report are tables summarizing the Committee’s recommendations for intakes and toxicological evaluations of the food additives and contaminants considered.
WHO technical report series, ISSN 0512-3054 947
Keywords: hodnocení rizik; Flavoring Agents; Food Additives; zemědělství a potravinářství; Food Contamination; kontaminace potravin; chuťové esence; Risk Assessment; potravinářské přísady